Unexplained Mysteries - Gunning, Thomas G. (Dodd, Mead, 1983)
Describes nine strange and, as yet, unexplained events including the man who lived after spending two days inside a whale's stomach, the sighting of a dinosaur-like creature in Africa, the moving coffins of Barbados.
Keywords: Curiosities and wonders; Juvenile literature; dept.rdg; faculty_collection